Indicators functional condition of sportsmen-handball player - Volodymyr Bogush; Sergiy Getmantsev; Olga Sokol; Oleksandr Kosenchuk; Olga Kuvaldina; Yevgen Yatsunskiy (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to investigate the functional state of the handball players to develop a comprehensive methodology for determining the prospects of athletes chosen sport. Material & Methods: the complex kinematics characteristics studied in girls of different age groups (15-16 years and 17-18 years) and sportsmanship, all 45 persons, according to our method of measuring the effect of coaching activities, as well as determined sensorimotor responses to auditory and visual stimuli, the air flow rate , accuracy of a given muscle force. Results: the changes of fitness and functional training athletes of all ages, and the professional development increases the chances of an athlete in the implementation of complex motor acts, which provides a set of actuators of various anatomical and physiological systems to achieve the desired final result. Conclusions: the change is due to the functional parameters of the general laws of growth and development and the influence of specific training and sports activities. The data obtained can be used to refine the physical activity at different levels of functional fitness, motor activity, morphological and functional capacity of the organism, the health of the athlete.